Correlative transmission electron microscopy and scanning electron microscopy of rabbit cornea. - Othman, Fauziah; Masrudin, Siti Saleha; Abd Ghafar, Norzana; Rahmat, Asmah; Saim, Aminuddin; Idrus, Ruszymah (Universiti Putra Malaysia, 2010)
The present work was carried out to study the organization of rabbit cornea. The transparent nature of the normal cornea was very important to give the understanding of the cornea in health and disease state. The ultrastructural features of the cornea were obtained by transmission electron microscopy and scanning electron microscopy. The epithelial surface of the cornea composed of microvilli and microplicae. In the Bowman's membrane, the individual collagen fibrils were interwoven densely to form a felt-like sheet, while in the stroma, the collagen fibrils ran abreast in lamellae. In the innermost stromal region adjacent to Descemet's membrane, collagen fibrils were oriented in various directions and interlaced, forming loose fibrillar networks. The endothelial layer is a single cell layer and apically-localized below the Descemet's membrane. This present work will be a standard reference for future research pertaining to cornea particularly cornea tissue engineering.